ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHIKETIMPANGAN PENDAPATAN DI PULAU SUMATERA TAHUN 2011-2015 - SARI, EMILDA, Eni Setyowati, S.E, M.Si (2017)
This research aims to analyze the influence of the local revenue, inflation and regional minimum wage against the inequality of income on the island of Sumatra. This type of research is a composite time series and cross section. Types of data used are secondary data with panel data type. The sample in this study was 10 provinces. Income inequality was measured using the Index result showed Williamson highest revenue Imbalances found in Riau Province and the lowest income inequality exists in the province of Bangka Belitung. Methods of data analysis used in this study is the regression of the panel. The most appropriate model of diipilih in this research is the Random Effect Method (REM). Based on the test results of F, simultaneously the variable local revenue, and the regional minimum wage effect on income inequality in Sumatra in 2011-2015. Determinant of the coefficients of test results (R2) showed that the magnitude of R-square value is 0.390569, or of 39,06%. This means that the variation of income inequality can be explained by the independent variables that exist in the model statistics like the local revenue (PAD), inflation (INF), and the regional minimum wage (UMR). While the rest of 60.94% is explained by other factors that are not included in the model. Based on a test of the validity of the influence (t-test) on significance (α) of 0.10, variable income asi area and regional minimum wage have a significant negative effect while the inflation variables have no effect on inequality of income on the island of Sumatra in 2011-2015.